Adaptive strategies and population ecology of northern grouse. - Bergerud, A. T.; Gratson, Michael W. (University of Minnesota Press, 1987)
This book is at once a major reference to the species of grouse that inhabit North America and the Holarctic and a synthesis of all the available data on their ecology, sociobiology, population dynamics, and management. The book undertakes to answer two long-standing questions in population ecology: what actually regulates the numbers within a population, and what are the breeding and survival strategies evolved in this northern environment? For Volume I, editors Arthur T. Bergerud and Michael W. Gratson have drawn together their own work and that of colleagues in North America, Iceland, and Norway - in all, eleven research studies, averaging six years' duration, on eight species of grouse. These studies deal with the blue and ruffed grouse of the forest habitat; the sharp-tailed grouse, prairie chicken, and sage grouse of the prairie or steppe; and the white-tailed, rick, and willow ptarmigan found in alpine and arctic tundras. The authors describe the rich repertoire of behavior patterns developed by the hen and the cock to achieve their two primary objectives - first, to stay alive, and then to breed. Volume II, primarily the work of Bergerud, synthesizes the evidence in Volume I and in the grouse research literature from a theoretical perspective. Several potentially controversial sociobiological hypotheses are advanced to account for flocking behavior, migration, dispersal, roosting and feeding behavior, mate choice and mating systems. The demographic analysis provides new insights into cycles of abundance, the limitation of numbers, and the demographic factors that determine densities. The contributors, besides Bergerud and Gratson: R. C. Davies, A. Gardarson, J. E. Hartzler, R. A. Huempfner, D. A. Jenni, D. H. Mossop, S. Myrberget, R. E. Page, R. K. Schmidt, W. D. Svedarsky, and J. R. Tester.